Władza komunistyczna wobec obchodów milenium chrztu Polski w archidiecezji wrocławskiej - Kazimiera Jaworska (Wrocławski Przegląd Teologiczny)
This paper introduces the activities of Lower Silesian party-state authorities and security services, the purpose of which was disruption to celebrations organized in Wrocław archdiocese in the year of millennium of the baptism of Poland in 1966. The activity of mentioned authorities within this scope was compatible with guidelines of the central government. Their main task was to undermine the authority of the Catholic Church and its hierarchs with particular consideration given to the primate Stefan Wyszyński and the archbishop of Wrocław diocese –archbishop Bolesław Kominek.